Pembenihan Ikan Nila (Oreochromis niloticus) di Bak Terpal Kecil dengan Rasio Kelamin Induk yang Berbeda - Bambang Sulistiyarto; R Restu; Ana Nopelia (JURNAL ILMU HEWANI TROPIKA (JOURNAL OF TROPICAL ANIMAL SCIENCE), 2021)
This study aims to develop a simple, inexpensive and suitable Nile tilapia (Oreochromis niloticus) hatchery technology for low-income communities.. This study evaluated the effectiveness of Nile tilapia hatchery in small tarpaulin tanks with different brood fish sex ratios. The study used a completely randomized design with 3 treatments and 3 replications. The treatment of this study was the ratio male-female of Nile tilapia broods, which included A (1:1), B (1:3), and C (1:5). Fish nursery used small tarpaulin tanks measuring 100 x 100 cm and a depth of 50 cm. The results showed that the average production of fry/female brood was significantly affected by the sex ratio of brood fish. The average production of fry/female was highest in the 1:1 ratio treatment (80.67 fry/female), while the treatment of 1:3 ratio (56.0 fish/female) and 1:5 ratio (49.67 fry/female) were not significantly different. The ratio male-female brood of 1:1 is the best for Nile tilapia fry production in small tarpaulin tanks. The condition of water quality in small tarpaulin tanks was still be tolerated by Nile tilapia, but the water quality was not optimal for Nile tilapia spawning. Water temperature ranges from 25 – 33 OC, dissolved oxygen 1.6 – 5.6 mg/L, and pH 5.59 – 7.68. Keywords : Nile tilapia (Oreochromis niloticus), sex ratio, brood fish, tarpaulin tank.